(untitled) (MATEMATIKA, 2018)
Riverbank filtration (RBF) system is a surface water technology that is based on the natural treatment of filtration instead of the use of chemicals, to pretreat surface water and provides public water supplies. Hydraulic conductivity value is one of the significant factors affecting the water quality in RBF systems. In this article, an analytical modelling is developed to investigate the effect of this parameter on one dimensional contaminant transport in RBF system. The model is solved by using Green’s function approach. The model is applied for the first RBF system conducted in Malaysia. Generally, the results show that increasing the hydraulic conductivity value lead to an increase in contaminant concentration in pumping well area.